2016
DOI: 10.1016/j.cell.2016.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Region-Specific Organoids Using Mini-bioreactors for Modeling ZIKV Exposure

Abstract: SUMMARY Cerebral organoids, three-dimensional cultures that model organogenesis, provide a new platform to investigate human brain development. High cost, variability and tissue heterogeneity limit their broad applications. Here we developed a miniaturized spinning bioreactor (SpinΩ) to generate forebrain-specific organoids from human iPSCs. These organoids recapitulate key features of human cortical development, including progenitor zone organization, neurogenesis, gene expression, and notably, a distinct hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

93
2,234
0
7

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,799 publications
(2,334 citation statements)
references
References 38 publications
93
2,234
0
7
Order By: Relevance
“…Consistent with that notion, improved uniformity is seen in the region‐specific organoid models which employ soluble neural inductive factors, but still there exist considerable variabilities 30, 31, 35. At least three reasons could account for them.…”
Section: Current Limitations Of Brain Organoidsmentioning
confidence: 71%
See 4 more Smart Citations
“…Consistent with that notion, improved uniformity is seen in the region‐specific organoid models which employ soluble neural inductive factors, but still there exist considerable variabilities 30, 31, 35. At least three reasons could account for them.…”
Section: Current Limitations Of Brain Organoidsmentioning
confidence: 71%
“…These studies have provided evidence that human neural stem cells are selectively vulnerable35, 48 and more susceptible to premature differentiation50 upon Zika virus infection, providing a molecular explanation for the observed microcephaly. A further study suggested activation of innate immune responses as a possible mechanism for Zika‐induced neuroprogenitor cell death 47.…”
Section: Translational Applications Of Brain Organoidsmentioning
confidence: 94%
See 3 more Smart Citations